2010
DOI: 10.1111/j.1399-3038.2010.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood infections and immunisation and the development of allergic disease in particular asthma in a high-risk cohort: A prospective study of allergy-prone children from birth to six years

Abstract: The role of early childhood infections and immunisation in the development of allergic diseases remains controversial. To examine these associations, six hundred and twenty infants with first-degree relatives with allergic diseases were recruited into the Melbourne Atopy Cohort Study. Information on risk factors and outcomes was collected by interviewer administered questionnaire and was based on parental report and/or a physician's diagnosis. Risk factors examined included early childhood infections (includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Cullinan et al [8] reported that the medical records of young adults with asthma showed a history biased to more gastrointestinal and less upper respiratory tract infection. Similarly a study of 6-year-old children found that children reported to have frequent recurrent gastrointestinal infection in the first 2 years of life had twice the risk of developing asthma [7]. Most of the infection at that age would be with rotavirus, an agent that can repeatedly infect children, being very prevalent in the study area.…”
Section: Discussionmentioning
confidence: 81%
“…Cullinan et al [8] reported that the medical records of young adults with asthma showed a history biased to more gastrointestinal and less upper respiratory tract infection. Similarly a study of 6-year-old children found that children reported to have frequent recurrent gastrointestinal infection in the first 2 years of life had twice the risk of developing asthma [7]. Most of the infection at that age would be with rotavirus, an agent that can repeatedly infect children, being very prevalent in the study area.…”
Section: Discussionmentioning
confidence: 81%
“…Otitis media with effusion is often a co-morbidity of AR and NAR and should be evaluated in all young children with rhinitis. Recent onset otitis media with effusion in children [44] or occurring in the first 2 years of life [45] is associated with rhinitis at 6 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…32 Lower rates of allergic symptoms and allergic sensitization have been found among children with measles, but no association was found between measles vaccination and allergic symptoms. 33 DT immunization was associated with asthma in one study, 34 …”
Section: T a B L E 2 Clinical Criteria For Diagnosing Anaphylaxis (Nimentioning
confidence: 99%